PELATIHAN KADER DALAM UPAYA MENINGKATKAN PENGETAHUAN TENTANG JAMINAN KESEHATAN NASIONAL - Edy Susanto; Sugiyanto Sugiyanto; Irmawati Irmawati; Sri Lestari (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2018)
Being a participant in the National Health Insurance (JKN) is one way to maintain good health for the citizens of Indonesia. JKN has been run by the Social Security Agency (BPJS) Health since January 1, 2014. BPJS planned that in 2014 the people of Indonesia who participated in the program of the National Social Security System (Navigation) and is targeted to reach 70% in 2019 to reach 100%.One of the benefits of national health insurance program is to improve the health and welfare of the community. However, not many people are aware of the importance of following the National Health Insurance program through participation BPJS. In addition, people are still confused in a groove in the service of the National Health Insurance.From the above issues, the Department of Medical Records and Health Information in cooperation with BPJS Semarang implement community service activities in the form of providing guidance, assistance, consultation on the National Health Insurance program. With this JKN coaching hoped that the people are able to understand the importance of participation JKN and improved health and welfare of the people especially in the region Wijaya Kusuma Posyandu RW: XXII, Village Meteseh, District Tembalang, Semarang.